ΜSR study of spin freezing and persistent spin dynamics in NaCaNi2F7. (29th August 2018) - Cai, Y; Wilson, M N; Hallas, A M; Liu, L; Frandsen, B A; Dunsiger, S R; Krizan, J W; Cava, R J; Rubel, O; Uemura, Y J; Luke, G M
Abstract: A new pyrochlore compound, NaCaNi2 F7, was recently synthesized and has a single magnetic site with spin-1 Ni 2+  . We present zero field and longitudinal field muon spin rotation ( μ SR) measurements on this pyrochlore. Density functional theory calculations show that the most likely muon site is located between two fluorine ions, but off-centre. A characteristic F- μ -F muon spin polarization function is observed at high temperatures where Ni spin fluctuations are sufficiently rapid. The Ni 2+ spins undergo spin freezing into a disordered ground state below 4 K, with a characteristic internal field strength of 140 G. Persistent Ni spin dynamics are present to our lowest temperatures (75 mK), a feature characteristic of many geometrically frustrated magnetic systems.